A One Health approach for the genomic characterization of antibiotic-resistant Campylobacter isolates using Nanopore whole-genome sequencing - Hurtado, Ana; Ocejo, Medelin; Oporto, Beatriz; Lavín, José Luis; Rodríguez, Ruth; Marcos, María Ángeles; Urrutikoetxea-Gutiérrez, Mikel; Alkorta, Miriam; Marimón, José María (Frontiers in Microbiology, 2025)
In response to the growing threat posed by the spread of antimicrobial resistance in zoonotic Campylobacter, a One Health approach was used to examine the genomic diversity, phylogenomic relationships, and the distribution of genetic determinants of resistance (GDR) in C. jejuni and C. coli isolates from humans, animals (ruminants, swine, and chickens), and avian food products collected during a regionally (Basque Country, Spain) and temporally (mostly 2021–2022) restricted sampling. Eighty-three C. jejuni and seventy-one C. coli isolates, most exhibiting resistance to ciprofloxacin and/or erythromycin, were whole-genome sequenced using Oxford Nanopore Technologies long-fragment sequencing (ONT). Multilocus sequence typing (MLST) analysis identified a high genomic diversity among isolates. Phylogenomic analysis showed that clustering based on the core genome was aligned with MLST profiles, regardless of the sample source. In contrast, accessory genome content sometimes discriminated isolates within the same STs and occasionally differentiated isolates from different sources. The majority of the identified GDRs were present in isolates from different sources, and a good correlation was observed between GDR distribution and phenotypic susceptibility profiles (based on minimum inhibitory concentrations interpreted according to the EUCAST epidemiological cutoff values). Genotypic resistance profiles were independent of genotypes, indicating no apparent association between resistance and phylogenetic origin. This study demonstrates that ONT sequencing is a powerful tool for molecular surveillance of bacterial pathogens in the One Health framework.